2014
DOI: 10.1007/s00018-014-1617-0
|View full text |Cite
|
Sign up to set email alerts
|

Current understanding of ZIP and ZnT zinc transporters in human health and diseases

Abstract: Zinc transporters, the Zrt-, Irt-like protein (ZIP) family and the Zn transporter (ZnT) family transporters, are found in all aspects of life. Increasing evidence has clarified the molecular mechanism, in which both transporters play critical roles in cellular and physiological functions via mobilizing zinc across the cellular membrane. In the last decade, mutations in ZIP and ZnT transporter genes have been shown to be implicated in a number of inherited human diseases. Moreover, dysregulation of expression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
172
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(177 citation statements)
references
References 178 publications
0
172
0
5
Order By: Relevance
“…Ten members of the ZnT family have been identified (ZnT1 to 10 -encoded by SL30A1 -10) and 14 members of the ZiP family (ZiP1-14, encoded by SLC39A1 -14). The expression of specific ZiPs and ZnTs is tissue-dependent and related to specific cellular functions [28]. For the purposes of this review we focus on transporters expressed in the pancreatic β cell.…”
mentioning
confidence: 99%
“…Ten members of the ZnT family have been identified (ZnT1 to 10 -encoded by SL30A1 -10) and 14 members of the ZiP family (ZiP1-14, encoded by SLC39A1 -14). The expression of specific ZiPs and ZnTs is tissue-dependent and related to specific cellular functions [28]. For the purposes of this review we focus on transporters expressed in the pancreatic β cell.…”
mentioning
confidence: 99%
“…Микроэле-ментное «голодание» провоцирует эссенциальный дисбаланс, потенцирует инкорпорацию и усиление отрицательного воздействия токсических и условно токсических микроэлементов, которые на фоне эко-номического прогресса, экологического состояния, промышленной и сельскохозяйственной деятельно-сти стали повсеместно распространенными и неотъ-емлемыми элементами окружающей среды. К таким биологическим «вредителям» можно отнести ртуть, свинец, мышьяк, никель, радиационный йод [20,25].…”
Section: таблицаunclassified
“…Zn homeostasis is regulated by two different Zn-transporter families: the Zrt-and Irt-like proteins (ZIPs; SLC39a) and the Zn transporter (ZnT) proteins (SLC30a). ZIPs facilitate the influx of Zn into the cytosol from the outside of cells or from the lumen of intracellular compartments whereas ZnTs ensure Zn efflux from the cytosol to the outside of cells or to intracellular organelles (15)(16)(17). ZnT1 is ubiquitously expressed and the only ZnT known to be involved in Zn efflux across the plasma membrane in many different cells, thus conferring resistance to Zn (15).…”
Section: Introductionmentioning
confidence: 99%
“…Previous findings have revealed that coordinated Zn mobilization by ZnTs is essential for the maintenance of Zn homeostasis. Thus, Zn plays roles in the regulation of critical physiological functions and profoundly affects health positively or negatively, as it is involved in a wide variety of diseases (17,24). The study of ZnTs is therefore receiving great clinical interest and attention at present (17), although little is known about the functional characteristics of ZnTs, particularly ZnT7, in endocrine tissues such as the mammalian testis.…”
Section: Introductionmentioning
confidence: 99%